Accounting for Climate Change in Rainfall Intensity-Duration-Frequency (IDF) Curves for Stormwater Management - Christopher Martinez; Young Gu Her; Eban Bean (EDIS)
This publication is meant to describe three major approaches to account for climate change in rainfall intensity-duration-frequency (IDF) curves and the pros and cons of each approach. This document aims to provide information to practicing engineers, Extension agents, and others interested in how projected changes in rainfall patterns can be considered for water resources management. Written by Christopher J. Martinez, Young Gu Her, and Eban Bean, and published by the UF/IFAS Department of Agricultural and Biological Engineering, January 2024.